Secrecy Capacity and Efficiency Outage Analysis of Cooperative PHY-Secure Wireless Systems and Secrecy Capacity-Based RIS Design - Tarun Jain; Sainath Bitragunta; Ashutosh Bhatia (IEEE Access)
Physical layer (PHY) security (PLS) leverages the inherent randomness of wireless fading channels to provide enhanced secrecy capacity. In this work, we consider a four-node, dual hop, eavesdropper-aware cooperative PHY-security model. Considering probabilistic relay selection and relaying in the presence of hybrid fading channels, we develop an insightful analysis for the probability of PHY-secrecy capacity outage (PSCO) and PHY-secrecy efficiency outage (PSEO). Specifically, we derive closed form expressions for these performance measures and evaluate them numerically to obtain valuable qualitative insights. We also develop an insightful comparative study to show that the cooperative PLS relay model having a destination node equipped with multiple antennas and performing selection combining delivers superior PHY-secrecy outage performance. We extend the analysis to the reconfigurable intelligent surface (RIS)-assisted cooperative PLS system. Specifically, we address the design problem of N, the number of reflecting elements in RIS. We develop insightful criteria based on secrecy capacity to derive a closed form lower bound on N. This insightful result provides the values of N that could achieve superior PHY-secrecy capacity than the relay-assisted cooperative PLS system. Our analysis of the former cooperative PLS model and its extension to RIS design is useful for next generation cooperative PLS relay and RIS-assisted wireless systems and networks.